Is Hermeneutics Necessary for Reading the Quran Today? - Mubarok, Akhmad Luthfi (Jurnal Indonesia Sosial Sains, 2025)
The debate over hermeneutics in Quranic studies remains a central discourse among contemporary Muslim academics. Hermeneutics is considered capable of bridging the revealed text with modern social realities, but at the same time has the potential to give rise to relativism of meaning and shift the authority of revelation. This study aims to weigh the potential and risks of hermeneutics in the study of interpretation and to offer a middle ground formulation called bounded hermeneutics . This study uses a qualitative method with a literature study approach, examining the main works of Abdullah Saeed, Nasr Hamid Abu Zayd, Amina Wadud, as well as the thoughts of Indonesian scholars such as Sahiron Syamsuddin, Quraish Shihab, and Abdurrahman Wahid. The analysis results show that hermeneutics contributes to presenting interpretations that are contextual and responsive to contemporary issues such as gender, human rights, and pluralism. However, this approach also has epistemological and social weaknesses when applied without limits. Through a synthesis between the principles of maqāṣid al- sharī'ah , the discipline of ushul al-tafsir , and the contextual sensitivity of hermeneutics, this research offers awake hermeneutics as a model of moderate interpretation that is relevant to the dynamics of the times but still maintains the sanctity of the divine text.